PERAN LEMBAGA KEUANGAN MIKRO SYARIAH DALAM PEMBERDAYAAN EKONOMI MASYARAKAT KECIL MENENGAH - JENITA JENITA (Prodi Manaj. Perbankan Syariah Fakultas Ekonomi dan Bisnis Islam – UIN Imam Bonjol Padang, 2017)
The theme of the article is the banks and financial institutions. Small and medium-sized enterprises desperately need the role of Sharia Microfinance Institutions primarily in terms of capital used to expand the market and expand its business so that it contributes greatly in the national economy. The role of Islamic microfinance institutions could have been tested and overcome the economic crisis for some time and even strengthened. UMKM including business units that rely heavily on LKMS in the long term for the good of the Indonesian economy, it is not surprising that many people are looking at LKMS, but the attention given has not fully addressed the fundamental issues facing LKMS so that it can really strengthen and develop a financing institution for UMKM are mainly small communities. Judging from the potential and funding sources that have been running, in fact LKMS has adequate funding in serving its customers and in the management of funds based on sharia. If the management of funds made by Islamic financial institutions can coordinate with each other, then it can be used as a great force.